(untitled) (Research, Society and Development, 2021)
Introduction: Neck pain is currently considered a very common condition. It affects about 50% of the entire population, with a predominance of females. In the academic context, the accumulation of required tasks, the time allocated to studies and the posture in cervical flexion related to the use of smartphones and computers, increase the probability of musculoskeletal disorders in the cervical region. Objective: To know the prevalence of neck pain in university students and its associated factors. Methodology: the databases chosen for this research were: PubMed, Science Direct, and Academic Google. Articles published from 2017 to 2021, in Portuguese and English, whose title, descriptors or abstract made reference to the theme were included. As exclusion criteria: articles that were not found in full, simple literature review and those that did not respond to the study proposal. Results and Discussion: Among the periods surveyed, six are international and four are national, which represents a shortage of Brazilian studies on this topic. Most data found a significant prevalence of neck pain in university students. Conclusion: There remains a relevant prevalence of neck pain in university students, which has directly affected their quality of life.